2018
DOI: 10.1038/s41419-018-0861-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells ameliorate hyperglycemia-induced endothelial injury through modulation of mitophagy

Abstract: Mitochondrial dysfunction and excessive mitochondrial reactive oxygen species (ROS) are fundamental contributors to endothelial injury in diabetic states. Mesenchymal stem cells (MSCs) have exhibited an extraordinary cytoprotective effect that extends to the modulation of mitochondrial homeostasis. However, the underlying mechanisms have not been clearly defined. Emerging evidence has suggested that mitophagy could counteract mitochondrial-derived oxidative stress through the selective elimination of impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…We also demonstrated that metformin activated SIRT3/PINK1/Parkin pathway could reverse the increased ROS level and loss of ΔѰM. Consistent with our results, studies have also shown that Parkin-mediated mitophagy may eliminate damaged mitochondria and decrease the level of ROS in human umbilical vein endothelial cells and fibroblasts (24,25).…”
Section: Discussionsupporting
confidence: 91%
“…We also demonstrated that metformin activated SIRT3/PINK1/Parkin pathway could reverse the increased ROS level and loss of ΔѰM. Consistent with our results, studies have also shown that Parkin-mediated mitophagy may eliminate damaged mitochondria and decrease the level of ROS in human umbilical vein endothelial cells and fibroblasts (24,25).…”
Section: Discussionsupporting
confidence: 91%
“…MSCs are found to ameliorate various diabetic complications, such as diabetic cardiomyopathy, retinopathy, nephropathy, peripheral neuropathy, and foot ulcer [33][34][35][36][37]. In our previous works, we also found that MSCs ameliorate hyperglycemia-induced endothelial injury [38,39] and diabetic kidney injury [40]. However, there are few papers that have reported the effects and potential mechanisms of MSCs on Sirt3 and diabetic lung injury.…”
Section: Introductionmentioning
confidence: 88%
“…To generate bone marrow MSCs, bone marrow mononuclear cells were harvested by flushing the tibiae and femurs of 3-week-old male Sprague-Dawley rats (50-55 g body weight) with phosphate-buffered solution (PBS). Bone marrow MSCs were cultured in complete medium (90% Dulbecco's modified Eagle's medium-low glucose+10% fetal bovine serum) (HyClone, Logan, USA) and grown with 5% CO 2 in a humidified atmosphere at 37°C, identified as described previously [39]. Bone marrow MSCs were passaged every 2 to 3 days and were used for transplantation at passage three or four.…”
Section: Isolation Of Bone Marrow Mscsmentioning
confidence: 99%
“…The increase of endothelial cell apoptosis is one of the primary characteristics of endothelial dysfunction (4) and one of the most important effects on HUVECs in high glucose conditions (46). The present data indicated that high glucose conditions induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%